Experimental investigation of an ecological concrete developed with calcareous silica brick and basalt fibers for the reduction of CDW - Escobar Jorge, Efraín (2024)
Lime silica bricks are one of the most predominant elements in construction and demolition waste, contributing significantly to the total solid waste produced worldwide. In Peru, the direct disposal of this waste in landfills prevails due to the lack of management alternatives and the lack of knowledge about sustainable options to use these materials. Simultaneously, the high CO2 emissions produced by the cement industries contribute substantially to global greenhouse gas emissions, giving rise to climate changes, melting of the Arctic ice, alterations in the biodiversity of animals and plants, droughts and others. phenomena. Recently, much research has been conducted on the use of supplementary cementitious materials to decrease cement production. This study focuses on evaluating a sustainable concrete by incorporating crushed calcareous silica brick waste and basalt fibers. To do this, consultation was carried out in different bibliographic sources on the properties of the materials and the optimal addition percentages. Following this, the dosage was carried out for a concrete of 34.34 MPa (350 kg/cm2). Four concrete mixtures with percentages of 5% and 10% of crushed calcareous silica brick reinforced with 0.5% basalt fibers were investigated. In addition, properties such as compressive strength and diametral tensile strength were analyzed at the ages of 7, 14 and 28 days. The results, in terms of mechanical performance, show a slight improvement of 2.1% compared to conventional concrete. In addition, control tests, including temperature, unit weight, air content and concrete slump, support the viability of the proposed concrete. Regarding the CO2 emissions reduction rates for sustainable concrete, a reduction of 56.33 kg of CO2 was obtained for each cubic meter of concrete.